Myanmar : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Myanmar. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation focuses on Myanmar's near- and medium-term challenges and policy priorities and was prepared before COVID-19 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. It, therefore, does not reflect the implications of these developments and related policy priorities. These developments have greatly amplified uncertainty and could heighten downside risks around the outlook. The IMF staff is closely monitoring the situation, including related policy responses from the authorities, and will continue to work on assessing its impact in the Myanmar economy. Although long-term prospects remain favorable, near-term growth is likely to remain below potential as the correction in real estate market and continued uncertainty weighs on investor sentiment in the runup to the 2020 elections. Starting FY2020/21, bank deleveraging will further slow credit and constrain gross domestic product growth as borrower's true ability to repay is revealed with term loans coming due and banks restructure in earnest.